Study on the Load Sharing Characteristic and Influential Factor of the Planetary Transmission of Vertical Mill Reducer - Wang Wuguang (Jixie chuandong)
Taking planetary gear pair time-meshing stiffness,meshing damping,bearing support stiffness,support damping of vertical mill reducer into consideration,the vibration differential equation of planetary gear transmission is set up based on lumped parameter method,the dynamic mesh force of each gear pair is obtained by adopting Runge-Kutta method. The sun gear of no floating and eccentricity error of sun gear,planet gear,gear ring are studied to get its effect on planetary transmission load sharing characteristic. The results indicate that floating of sun gear has significant impact on planetary transmission load sharing characteristic. Considering the only factor of sun gear eccentricity error,gear ring eccentricity error separately has better load sharing characteristic than complex considering eccentricity error of sun gear,planetary gear and ring gear,the eccentricity error has little effect on load sharing characteristic,when the sun gear is no floating,the load sharing characteristic of system will be worse.